Comparative Study of Learning Activities between High School Students in Rural and Urban Physiographic Terrain in Geography Learning in Badung Regency - Ayu Ramantari, Putu Amanda; Astra Wesnawa, I Gede; Dwipayana, Made (Journal of English Language and Education, 2025)
The results of research conducted at SMA Negeri 1 Mengwi and SMA Negeri 1 Kuta Utara showed differences in student learning activities in geography learning between rural and urban areas in Badung Regency. This study aims to compare students' learning activities by using comparative quantitative research methods. Data collection techniques were conducted through observation, questionnaires, and documentation, then analyzed using descriptive techniques and hypothesis testing. Based on the analysis, it was found that the average student learning activity in urban areas was higher than that in rural areas. The larger standard deviation in urban areas indicates a wider variety of learning activities than in rural areas. The distribution of learning activity categories also shows that more students in urban areas fall into the “high” and “very high” categories compared to students in rural areas. Hypothesis testing results show significant differences between students' learning activities in the two regions. This finding is an important basis in formulating more effective and contextualized learning strategies according to the characteristics of each region.